KAJIAN DEBIT DAN SEDIMENTASI DI KAWASAN HULU SUB DAERAH ALIRAN SUNGAI (DAS) KOMERING SUMATERA SELATAN - Satria Jaya Priatna; M. Edi Armanto; Edward Saleh; Dinar Putranto; Fauzanul H. Fikry (Faculty of Agricultural Technology, University of Jember, 2011)
This study aims to identify and know the discharge of water and sedimentation in the area Upper of Sub-Das Komering South Sumatera. The results of study indicate the biophysical conditions of the majority Sub-watershed upstream relative Komering particularly disturbed hydrological conditions, which thought caused by the expansion of the clearing for various activities with land use patterns that are less appropriate. The average value river discharge of water in Sub watershed Komering ranged from 0.89 to 1566.51 m3/second. The average value of the largest river discharge in the river there Komering, while the average value of the smallest river discharge in the river there Kejantor. Total sediment load in each sub-sub Komering upstream watershed is approximately 140,721.73 tons / day, but the sediment load in rivers measured at the main Komering only about 128,579.14 tons / day then there is still a difference of approximately 12142.6 tons / day , is expected because of the large load of sediment that settles on the way of water from upstream into the river Komering.Keywords: discharge of water , sedimentation; Komering watershed